Can GnRH Be Used to Induce Ovulation Early in Lactation and Improve Fertility in Dairy Cows? - Klibs N. Galvão (EDIS)
It is well established that early cyclicity results in increased pregnancy per artificial insemination and decreased time to pregnancy. But none of the previous studies have used synchronization programs such as the Presynch-Ovsynch as part of their reproductive management. This 2-page fact sheet presents the results of a recent paper that evaluated the effects of administration of GnRH at 17 ± 3 and 20 ± 3 DIM in Holstein dairy cows without a corpus luteum (CL) on induction of ovulation, uterine health, and reproductive outcomes. Written by Klibs N. Galvão and published by the UF Department of Veterinary Medicine-Large Animal Clinical Sciences, July 2014.